(untitled) (Revista Contexto & Saúde, 2020)
Objective: To conduct a systematic review of scientific evidence on the effects of probiotic and symbiotic supplementation in patients with non-alcoholic fatty liver disease. Method: This is a systematic review study conducted in the MedLine databases via PubMed, Web of Science and Scopus, in June 2020, using the following descriptors: non-alcoholic liver disease, probiotics, synbiotic. After applying the eligibility criteria, 12 articles remained. Results: Probiotic and symbiotic supplementation has shown promising results in non-alcoholic fatty liver disease, most clinical trials analyzed demonstrated reduced serum concentration of liver enzymes, improved lipid profile and decreased degree of hepatic steatosis. Conclusion: There are still few published clinical trials and studies have been conducted with different species of probiotic and prebiotic strains, dose and intervention time, so there is no specific indication for supplementation. Further studies are suggested to clarify the effectiveness of probiotics and symbiotics in non-alcoholic fatty liver disease.